First steps in forecasting the health workforce in Kazakhstan: A baseline scenario - Berik Koichubekov; Azamat Kharin; Bauyrzhan Omarkulov; Marina Sorokina; Ilya Korshukov; Nazgul Omarbekova (National Scientific Medical Center, 2021)
Background: The purpose of this study was to consider the basic scenario for predicting the need for general practitioners in Kazakhstan until 2030. Material and methods: A basic health care human resource planning model consists of supply and demand components, analysis of the outcomes of the prediction, and planning future actions. Stock-flow consistent model was built by using current situation and projected Kazakhstan population, retirement rate, attrition rate and adding the estimated number of new graduates. Results: According to the proposed scenario, in some years of the forecast period, both an excess and a lack of a general practitioners offer are possible. The largest surplus, 226 doctors, is predicted in 2024. However, starting in 2027 their shortage is possible, with a peak of 339 general practitioners in 2030. Conclusion: Considered scenario leads to the fact that inflow does not cover the increasing needs of primary health care associated with population growth. In this case, our forecast is the basis for medical schools to adjust the number of general practitioners students in internship, seeking a balance of supply and demand.